Perancangan aplikasi belajar bahasa inggris berbasis website - Asa Dilla Safitri; Atik Sulami; Jamilatun Safitri; Dwi Hartanti (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2023)
In times of a pandemic like this, all learning activities are carried out online via the internet with the help of learning applications that can support one's education. In the current era, there is a great need for interactive distance learning applications. An interactive English learning application in web form will be easily accessed and used by anyone. Therefore, on this occasion we created a website-based learning application, especially for English subjects because that language is an international language. In this research, an English learning application will be built that can be run on a web-based basis. The material displayed in this application is tenses, listening, speaking, idioms, expressions, regular and irregular verbs, and slang. This application is designed with UML modeling, developed using HTML programming language. We also use the waterfall software process model in designing the BeBI (Learning English) application system. The purpose of making this application is to make it easier to learn English with material that is easy to understand and this application has an easily accessible interface. The waterfall model that we use is the Sommerville waterfall with the consideration that the system design steps will be organized, focused, and easy to follow. Where the result of designing this application is an educational application system for users which is expected to help the community in learning English and make it easier for someone to prepare themselves to take English tests such as TOEFL and TOEIC. For further development, it is hoped that this application can be accessed on various platforms.